2000
DOI: 10.1111/1467-9469.00182
|View full text |Cite
|
Sign up to set email alerts
|

Independence Structure of Natural Conjugate Densities to Exponential Families and the Gibbs' Sampler

Abstract: In this paper the independence between a block of natural parameters and the complementary block of mean value parameters holding for densities which are natural conjugate to some regular exponential families is used to design in a convenient way a Gibbs' sampler with block updates. Even when the densities of interest are obtained by conditioning to zero a block of natural parameters in a density conjugate to a larger``saturated'' model, the updates require only the computation of marginal distributions under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…However, Wang and Li (2012) demonstrated that a block Gibbs sampler (Piccioni, 2000) convincingly outperforms other methods. We now describe the block Gibbs sampler, and suggest a simple modification to improve efficiency in high dimensions.…”
Section: Bayesian Inference In Gwishart-based Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Wang and Li (2012) demonstrated that a block Gibbs sampler (Piccioni, 2000) convincingly outperforms other methods. We now describe the block Gibbs sampler, and suggest a simple modification to improve efficiency in high dimensions.…”
Section: Bayesian Inference In Gwishart-based Modelsmentioning
confidence: 99%
“…The GWishart block Gibbs sampler (Piccioni, 2000;Wang and Li, 2012) is based on the fact that a block of Λ corresponding to a clique in G can be sampled conditional on the rest of Λ by sampling from a Wishart. Thus, given a set of cliques that cover Λ V , a sampler for the GWishart can be constructed by iterating over the covering set and conditionally sampling each block of Λ.…”
Section: Sampling the Gwishart With Block Gibbsmentioning
confidence: 99%
“…This sampling method is called the block Gibbs sampler and was originally discussed by Piccioni (2000). Asci and Piccioni (2007) developed it explicitly by exploiting the theory of exponential families with cuts.…”
Section: The Block Gibbs Samplermentioning
confidence: 99%
“…The sequence of matrices (K r ) r≥r 0 generated by the block Gibbs sampler are random samples from W G (δ, D) after a suitable burn-in time r 0 (Piccioni 2000;Asci and Piccioni 2007). Carvalho, Massam, and West (2007) proposed another sampler that is based on decomposing G into its sequence of prime components.…”
Section: The Block Gibbs Samplermentioning
confidence: 99%
“…The Bayesian IPF is extremely similar to the classical IPF algorithm, except that sequentially updating the parameters θ based on each fixed marginal is replaced with an adjustment based on a marginal table with the same structure whose entries have been drawn from Gamma distributions with certain shape parameters. Piccioni (2000) exploits the theory of regular exponential families with cuts to formally construct a Gibbs sampler algorithm for sampling from their natural conjugate densities. Asci and Piccioni (2007) give an extension to improper target distributions.…”
Section: The Bayesian Iterate Proportional Fitting Algorithmmentioning
confidence: 99%